GEOGRAFIA SIMBOLICĂ ŞI MONARHIA CONSTITUŢIONALĂ ÎN ROMÂNIA. SAU DE CE 1989 NU A FOST 1866 - Dungaciu, Dan (Revista de Știinţe Politice şi Relaţii Internaţionale)
The article presents and reevaluates the great and old Romanian political debate: republic vs. monarchy. Starting from the central value of the concept of strategic positioning in a „symbolic geography“, it argues that, by restoring the constitutional monarchy after 1989, Romania and Romanians would have reintegrated much more easily and more durable into the European democratic order of which they had been part for centuries.